2015
DOI: 10.1002/jms.3709
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐, di‐ and trimethylated homologues of isoprenoid tetraether lipid cores in archaea and environmental samples: mass spectrometric identification and significance

Abstract: Higher homologues of widely reported C(86) isoprenoid diglycerol tetraether lipid cores, containing 0-6 cyclopentyl rings, have been identified in (hyper)thermophilic archaea, representing up to 21% of total tetraether lipids in the cells. Liquid chromatography-tandem mass spectrometry confirms that the additional carbon atoms in the C(87-88) homologues are located in the etherified chains. Structures identified include dialkyl and monoalkyl ('H-shaped') tetraethers containing C(40-42) or C(81-82) hydrocarbons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 65 publications
5
29
1
Order By: Relevance
“…The novel 2G-methylated GDGT (2G-Me-GDGT; IPL-14) and 2G-dimethylated GDGT (2G-diMe-GDGT; IPL-15) were identified by exact masses after Q-TOF-MS and MS/MS fragmentation patterns (Table 2; Figure 3), which were consistent with the Me-GDGT core lipids reported by Knappy et al (2009) and Knappy (2010). These methylated core lipids (i.e., 1316.3Da and 1330.4 Da, respectively) were generated via removal of the 2G headgroups after mild acid hydrolysis (Meador et al, unpublished data) and co-eluted with GDGT (1302.2 Da) during normal phase chromatography, further confirming that the additional methyl group was located in the biphytanyl chain and not in the glycerol moiety (Zhu et al, 2014).…”
Section: Resultssupporting
confidence: 84%
“…The novel 2G-methylated GDGT (2G-Me-GDGT; IPL-14) and 2G-dimethylated GDGT (2G-diMe-GDGT; IPL-15) were identified by exact masses after Q-TOF-MS and MS/MS fragmentation patterns (Table 2; Figure 3), which were consistent with the Me-GDGT core lipids reported by Knappy et al (2009) and Knappy (2010). These methylated core lipids (i.e., 1316.3Da and 1330.4 Da, respectively) were generated via removal of the 2G headgroups after mild acid hydrolysis (Meador et al, unpublished data) and co-eluted with GDGT (1302.2 Da) during normal phase chromatography, further confirming that the additional methyl group was located in the biphytanyl chain and not in the glycerol moiety (Zhu et al, 2014).…”
Section: Resultssupporting
confidence: 84%
“…The high abundances of GTGTs in HWCG‐III Thaumarchaeota are unprecedented among cultivated archaea (Table ; cf. De Rosa and Gambacorta, ; Knappy et al ., ; Feyhl‐Buska et al ., ) and have previously been interpreted to reflect sub‐optimal growth conditions of Ca. N. yellowstonii (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The recent identification of butanetriol and pentanetriol dialkyl glycerol tetraethers (BDGTs and PDGTs, Knappy et al, 2014;Zhu et al, 2014), in which one glycerol is substituted by a butanetriol or pentanetriol, challenges this assumption. Tandem mass spectrometry complemented with gas chromatography (GC) detection of butanetriol after hydrolysis (Zhu et al, 2014) demonstrated the presence of a 1,2,3 butanetriol backbone in BDGTs but did not specify its configuration within the lipid molecule, notably its linkages with the biphytanyl side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Tandem mass spectrometry complemented with gas chromatography (GC) detection of butanetriol after hydrolysis (Zhu et al, 2014) demonstrated the presence of a 1,2,3 butanetriol backbone in BDGTs but did not specify its configuration within the lipid molecule, notably its linkages with the biphytanyl side chains. Subsequently, BDGTs and PDGTs were observed in diverse samples, both as intact polar lipids (IPLs, lipids with polar headgroups) and core lipids (CLs, lipids without polar headgroups), from recent organic-rich estuarine sediments (Meador et al, 2015) to old Jurassic marine shales (Knappy et al, 2014) and deep subsurface sediments (Becker et al, 2016;Zhu et al, 2014). Furthermore, Becker et al (2016) identified BDGTs as prominent membrane lipids in Methanomassiliicoccus luminyensis, currently the only cultured representative of the seventh order of methanogens; lesser quantities of PDGTs were also observed in this archaeon.…”
Section: Introductionmentioning
confidence: 99%